GROUND MOTION PREDICTION EQUATIONS FOR MALAYSIA DUE TO EARTHQUAKES IN SUMATRAN REGION - AULOV, AZIZ (2014)
This research comes as a part of the recent initiatives in Malaysia to assess the hazard posed by earthquakes. There have been numerous seismic hazard studies so far that included Malaysian territories, thus there was a need to assess how reliable those studies are. Two main potential contributors to error were identified: 1) seismic hazard analysis method 2) ground motion prediction equation (GMPE). The amount of variations in predictions a faulty GMPE can produce is huge, thus this research concentrates on assessing the available GMPEs and generating one specific for Malaysia.